Conversion of bamboo to sugars by dilute acid and enzymatic hydrolysis - Tippayawong,N. (International Journal of Renewable Energy Research, 2015)
Lignocellulosic biomass is an important alternative energy source to be utilized for ethanol production. In this work, bamboo (Dendrocalamus asper Backer) was used as biomass feedstock for conversion to fermentable sugars. Pretreatment was carried out with dilute sulfuric acid at concentrations between 0.4 - 1.6% w/w, and residence time between 45 - 135 min at a fixed temperature of 140°C. Prehydrolyzate was later analyzed for total sugars by high performance liquid chromatography. For the conditions considered, maximum glucose and xylose yields after chemical treatment were obtained from bamboo to be 25.8 and 16.9 mg/mL, respectively. Water insoluble solids obtained were subsequently hydrolysed with cellulase (Trichoderma reesei) and β-glucosidase (Novozyme 188) for 72 h. It was found that increasing yields were obtained with increasing acid concentrations and residence times. The effects of pretreatment severity and enzymatic hydrolysis greatly increased the sugar concentrations after the hydrolysis.